Multinationals in the blue economy: Navigating through Sustainable Development Goals - López-Morales, José Satsumi; Angulo Valenzuela, Alan Enrique (RAN - Revista Academia & Negocios, 2025)
Purpose: to identify which SDGs have been addressed by the main multinational companies of the blue economy. Methodology: the annual reports of 41 multinationals that carry out activities in the oceans were reviewed. For its analysis, the qualitative research software Atlas.ti was used, where the texts of these reports were analyzed through codes. Results: the most represented SDGs are 7 and 9. The conclusion was to indicate a lack of alignment between their activities and their impact on the ocean, focusing on activities specific to their sector of economic activity. Implications: it is important that the MNEBE consider more policies and practices related to the environment, especially due to the nature of their operation in the ocean. The second practical implication is that decision makers in companies can carry out periodic evaluations on the progress of achieving the SDG goals in their activities. Originality: to study the multinationals of the blue economy and its relationship with Sustainable Development Goals.